High-Efficiency Diphenylpyrimidine Derivatives Blue Thermally Activated Delayed Fluorescence Organic Light-Emitting Diodes - Sohn, Sunyoung; Ha, Min Woo; Park, Jiyong; Kim, Yoo-Heon; Ahn, Hyungju; Jung, Sungjune; Kwon, Soon-Ki; Kim, Yun-Hi (Frontiers in Chemistry, 2020)
Organic light-emitting diodes with thermally activated delayed fluorescence emitter have been developed with highly twisted donor–acceptor configurations and color-pure blue emitters. Synthesized 4-(4-(4,6-diphenylpyrimidin-2-yl)phenyl)-10H-spiro[acridine-9,9′-fluorene] (4,6-PhPMAF) doped device with spiroacridine as a donor unit and diphenylpyrimidine as acceptor exhibits the device characteristics such as the luminescence, external quantum efficiencies, current efficiencies, and power efficiencies corresponding to 213 cd/m2, 2.95%, 3.27 cd/A, and 2.94 lm/W with Commission International de l'Eclairage (CIE) coordinates of (0.15, 0.11) in 4,6-PhPMAF-doped DPEPO emitter. The reported 10-(4-(2,6-diphenylpyrimidin-4-yl)phenyl)-10H-spiro[acridine-9,9′-fluorene] (2,6-PhPMAF) doped device exhibit high device performance with 1,445 cd/m2, 12.38%, 19.6 cd/A, and 15.4 lm/W, which might be originated from increased internal quantum efficiency by up-converted triplet excitons to the singlet state with relatively smaller ΔEST of 0.17 eV and higher reverse intersystem crossing rate (kRISC) of 1.0 ×108/s in 2,6-PhPMAF than 0.27 eV and 3.9 ×107/s in 4,6-PhPMAF. Despite low performance of 4,6-PhPMAF doped device, synthesized 4,6-PhPMAF has better color purity as a deep-blue emission with y axis (0.11) than reported 2,6-PhPMAF with y axis (0.19) in CIE coordinate. The synthesized 4,6-PhPMAF has higher thermal stability of any transition up to 300°C and decomposition temperature with only 5% weight loss in 400°C than reported 2,6-PhPMAF. The maximum photoluminescence emission of 4,6-PhPMAF in various solvents appeared at 438 nm, which has blue shift about 20 nm than that of 2,6-PhPMAF, which contributes deep-blue emission in synthesized 4,6-PhPMAF.